(untitled) (Journal Of Educational and Psychological Researches, 2014)
The unemployment is considered from the most danger problems that our society face them in current time & in the near future , because it makes prodigality for element of human being , particularly age of youth who have ability to work & producing , that resulted in negative effects forecast to dire consequences social and economical dangers . In the same time as will be stated in our explanation in the following in our research , because the unemployment has ability to help to prepare good environment to grow crime , actions of violence that mostly are main cause to decrease living level of majority of citizens & in increasing numbers who became under poverty , the unemployment is economical problem as it is psychological , social , security and political problem In the light of these developing , the necessity required to adopt limits of strategies to combat unemployment , the reply is taken to treat real causes of represented unemployment by financial & administrative corruption , and non conformity between teaching system & market of labor , and finiteness private sector , lowering rehabilitation & security deterioration , to enable human capital to perform his active role in processes of building and production The researches & studies have great role in multiple of choices & solutions at specialists in executive & legislative systems of the state to shorten time & road to what these studies & theoretical researches as practical save them of database may be close & touch to reality , that grant it flexibility & more facility to set current & future solutions & strategies to combat unemployment & treat its causes or contracting and decreasing it